Clinical characteristics and short-term outcomes of multisystem inflammatory syndrome in a country with a high prevalence of KD - You, Sung Doo; Kim, Jin Ho; You, Jihye (Frontiers in Pediatrics, 2023)
Background The COVID-19 pandemic has spread continuously. Multisystem inflammatory syndrome in children (MIS-C), like Kawasaki disease (KD), is a potentially severe illness in children that appears to be a delayed, post-infectious complication of COVID-19. However, based on the relatively low MIS-C prevalence and high KD prevalence in Asian children, the clinical features of MIS-C are not fully recognized, especially after the spread of the Omicron variant. Here, we aimed to identify the clinical characteristics of MIS-C in a country with high KD prevalence. Methods We retrospectively analyzed 98 children diagnosed with KD and MIS-C admitted to Jeonbuk National University Hospital between January 1, 2021, and October 15, 2022. Twenty-two patients were diagnosed with MIS-C, following CDC diagnostic criteria for MIS-C. We reviewed medical records for clinical features, laboratory findings, and echocardiography. Results Age, height, and weight were higher for patients with MIS-C than for those with KD. Lymphocytes percentage was lower, and the segmented neutrophil percentage was higher in the MIS-C group. The inflammation marker C-reactive protein was higher in the MIS-C group. Prothrombin time was prolonged in the MIS-C group. Albumin level was lower in the MIS-C group. The MIS-C group had lower potassium, phosphorus, chloride, and total calcium. Twenty-five percent of patients diagnosed with MIS-C had positive RT-PCR, and all the patients were N-type SARS-CoV-2 antibody-positive. Albumin ≤3.85 g/dL effectively predicted MIS-C. Regarding echocardiography, the right coronary artery z-score, the absolute value of apical 4-chamber left ventricle longitudinal strain, and the ejection fraction (EF) was significantly lower in the MIS-C group. A month after diagnosis using echocardiographic data, all coronary artery z-scores had reduced significantly. EF and fractional shortening (FS) also improved one month after diagnosis. Conclusion Albumin values can differentiate MIS-C and KD. In addition, a decrease in the absolute LV longitudinal strain value, EF, and FS was observed in the MIS-C group using echocardiography. Coronary artery dilatation was not evident at the initial diagnosis; however, a change in coronary artery size, EF, and FS was observed on follow-up echocardiography a month after diagnosis.